STRATEGI GURU DALAM MENINGKATKAN PEMBELAJARAN PAI SISWI KELAS XI SMA AL-RIFA’IE GONDANGLEGI - Umi Tartilah; Muhammad Hanif; Ika Anggraheni (VICRATINA, 2019)
With the existence of qualified teachers, an educational institution can be qualified. From the background of the research above, the researcher formulated the problem, namely how about learning PAI in the classroom, the strategies or efforts of the teacher how to improve PAI learning, what factors support and inhibit the teacher in improving learning. with the aim of describing PAI learning. strategies or efforts or steps of the teacher in improving PAI learning, and describing the supporting and inhibiting factors of teachers in improving PAI learning. The study was conducted using qualitative research. The study used the method of observation, interviews, and documentation. The results of this study are PAI learning using three programs, namely intraturicular, extracurricular, and co-curricular. Based on the findings of the teacher researchers provide strategies to students in the form of organizational strategies, learning strategies, and management strategies.